ADA/CD26 axis increases intra-tumor PD-1+CD28+CD8+ T-cell fitness and affects NSCLC prognosis and response to ICB - Ornella Franzese; Belinda Palermo; Giuseppe Frisullo; Mariangela Panetta; Giulia Campo; Daniel D’Andrea; Isabella Sperduti; Riccardo Taje; Paolo Visca; Paola Nisticò (OncoImmunology)
Improving cancer immunotherapy efficacy hinges on identifying key T-cell populations critical for tumor control and response to Immune Checkpoint Blockade (ICB). We have recently reported that while the co-expression of PD-1 and CD28 is associated with impaired functionality in peripheral blood, it significantly enhances T-cell fitness in the tumor site of non-small cell lung cancer (NSCLC) patients. To uncover the underlying mechanisms, we explored the role of CD26, a key player in T-cell activation through its interaction with adenosine deaminase (ADA), a crucial intra/extracellular enzyme able to neutralize local adenosine (ADO). We found that an autocrine ADA/CD26 axis enhances CD8+PD-1+CD28+ T-cell function, particularly within an immunosuppressive environment marked by CD39 expression. Then, we interrogated the TCGA and OAK datasets to gain insight into the prognostic/predictive potential of our findings. We identified a signature predicting overall survival (OS) in LUAD patients and response to atezolizumab in advanced LUAD cases. These findings suggest promising avenues for therapeutic intervention targeting the ADA/CD26 axis.